Neural Dynamics of Creative Movements During the Rehearsal and Performance of “LiveWire" - Maxine Annel Pacheco-Ramírez; Mauricio A. Ramírez-Moreno; Komal Kukkar; Nishant Rao; Derek Huber; Anthony K. Brandt; Andy Noble; Dionne Noble; Bryan Ealey; Jose L. Contreras-Vidal (Scientific Data)
Abstract This report contains a description of physiological and motion data, recorded simultaneously and in synchrony using the hyperscanning method from two professional dancers using wireless mobile brain-body imaging (MoBI) technology during rehearsals and public performances of “LiveWire” - a new composition comprised of five choreographed music and dance sections inspired by neuroscience principles. Brain and ocular activity were measured using 28-channel scalp electroencephalography (EEG), and 4-channel electrooculography (EOG), respectively; and head motion was recorded using an inertial measurement unit (IMU) placed on the forehead of each dancer. Video recordings were obtained for each session to allow for tagging of physiological and motion signals and for behavioral analysis. Data recordings were collected from 10 sessions over a 4-month period, in which the dancers rehearsed or performed (in front of an audience) choreographed expressive movements. A detailed explanation of the experimental set-up, the steps carried out for data collection, and an explanation on the usage are provided in this report.